2018
DOI: 10.1111/cga.12316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of dentocraniofacial characteristics in patients with Williams syndrome

Abstract: Williams syndrome (WS) is a rare congenital anomaly that is characterized by distinctive facial features, congenital heart disease, and behavioral characteristics that include mental retardation. However, only a few reports have documented the dentocraniofacial morphological characteristics of WS in Japanese individuals. The aim of this study was to analyze the dentocraniofacial morphology and growth patterns in a group of nine Japanese subjects (two males and seven females; mean age at admission, 10.1 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
4
10
2
Order By: Relevance
“…Matsuno et al reported comparable findings on the lower incisors and mandible of Japanese individuals with WBS. 19 In contrast to the study of Axelsson et al, we did not find significant differences in the length of the posterior cranial base between male and female subjects. 20 Most WBS subjects in our study presented dental hypoplasia and slender or short roots.…”
Section: Ta B L E 1 Cephalometric Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Matsuno et al reported comparable findings on the lower incisors and mandible of Japanese individuals with WBS. 19 In contrast to the study of Axelsson et al, we did not find significant differences in the length of the posterior cranial base between male and female subjects. 20 Most WBS subjects in our study presented dental hypoplasia and slender or short roots.…”
Section: Ta B L E 1 Cephalometric Resultscontrasting
confidence: 99%
“…Cephalometric analysis of our sample showed differences involving the lower lip and lower incisors, which were significantly more proclined in WBS subjects. Matsuno et al reported comparable findings on the lower incisors and mandible of Japanese individuals with WBS 19 . In contrast to the study of Axelsson et al, we did not find significant differences in the length of the posterior cranial base between male and female subjects 20 …”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In terms of cranial morphology, microcephaly was very common. 16 Figure1. Cranial imaging of a microcephaly patient *Microcephaly and trigonocephaly can be seen on cranial X-ray (yellow arrow).…”
Section: Discussionmentioning
confidence: 99%